Influence of Feed Form on Dietary Lysine and Energy Intake and Utilization of Broilers from 14 to 30 Days of Age - Greenwood, M.W.; Cramer, K.R.; Clark, P.M.; Behnke, K.C.; Beyer, R.S. (International Journal of Poultry Science, 2004)
An experiment was conducted to evaluate the effects of feed form on lysine and dietary energy levels necessary for maximum body weight gain (BWG) and feed efficiency (FE) of male broilers from 14 to 30 d and to determine if birds realize a benefit in productive energy from consuming pelleted diets. A 2 x 3 x 2 factorial treatment arrangement was achieved by feeding diets in two forms (mash and steam-conditioned pellets) with three levels of digestible lysine (0.85, 0.95 and 1.05 % of the diet) and two dietary energy levels (3050 and 3200 kcal ME/kg). Male broiler chicks were provided a nutritionally adequate diet (3100 kcal ME/kg and 22.7% CP) from 0-13 d. Four pens of 32 birds were fed each dietary treatment. Mean body weight and feed consumption were obtained at 14 and 30 d. Average feed intake (AFI) was used to calculate lysine conversion ratio and calories consumed per bird. Pellet-fed birds consumed significantly less digestible lysine (P=0.0061) to achieve the same amount of BWG as the mash-fed birds. Pellet-fed birds exhibited a linear increase in BWG (P=0.0188) with increasing lysine concentrations, while mash-fed birds did not display a growth response at digestible lysine levels greater than 0.85%. Birds fed 3200 kcal ME/kg diets had greater BWG (P=0.006) than those fed 3050 kcal diets. No feed form x dietary energy level interaction was observed for any parameter. Feed form had no effect on AFI (P=0.3784). These findings suggest that improved BWG obtained with pelleted diets may be the result of reduced energy expenditure during meal consumption, indicating that feed form may influence perceived nutrient needs.